2014
DOI: 10.1097/ta.0000000000000218
|View full text |Cite
|
Sign up to set email alerts
|

Defining the optimal time to the operating room may salvage early trauma deaths

Abstract: Epidemiologic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 9 publications
0
30
1
Order By: Relevance
“…Harvin et al 24 found that hypotensive trauma patients requiring emergent laparotomy (within 90 minutes of admission) had a 46% mortality; 65% of those deaths were related to hemorrhage. In another study looking at trauma deaths within 4 hours of admission, 50% of patients died within the first hour 15. In our study, OR placement was associated with longer time to AO (75 minutes vs. 23 minutes), although location of placement and time to AO were not associated with increased in-hospital mortality after controlling for admission physiology and GCS score.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Harvin et al 24 found that hypotensive trauma patients requiring emergent laparotomy (within 90 minutes of admission) had a 46% mortality; 65% of those deaths were related to hemorrhage. In another study looking at trauma deaths within 4 hours of admission, 50% of patients died within the first hour 15. In our study, OR placement was associated with longer time to AO (75 minutes vs. 23 minutes), although location of placement and time to AO were not associated with increased in-hospital mortality after controlling for admission physiology and GCS score.…”
Section: Discussioncontrasting
confidence: 51%
“…Because the median time to death from severe hemorrhage is approximately 1 hour,15 there is now appropriate emphasis on shortening the time to hemostasis as much as possible 5. Currently, the majority of REBOA catheters are placed either in the emergency department (ED) or the operating room (OR) 16.…”
Section: Introductionmentioning
confidence: 99%
“…Immediate surgical/radiological intervention for hemostasis is a key component of management in hemorrhagic trauma 1,2 . Immediate blood transfusion to maintain hemodynamics and adequate tissue oxygenation is often needed 3 .…”
Section: Introductionmentioning
confidence: 99%
“…A reduced time to intervention is well known to be associated with decreased mortality, such as in acute coronary syndrome [7] and trauma [8]. The effect of reduced time to embolization among hemodynamically unstable patients with pelvic fracture has been described [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%